An Integration Scenario of Visa and Residence Permit in Indonesia during Covid-19 Outbreak: A Policy Learning from Australia - Dede Lalan Maulana; Ridwan Arifin (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2021)
Indonesian visa and residence permits have separated functions, where a visa is an approval to enter, but a residence permit is to stay in Indonesia. Today’s Onshore and offshore visa policy is the DGI’s breakthrough in rolling out an online visa application process to grant an electronic visa that is not integrated with residence permit functions. This study looks into a visa scheme and an integration scenario of visa and residence permit that responds to the Covid-19 outbreak in Indonesia. Using a policy analysis and policy learning from the Australian Government, this study proposes the functional integration between the Indonesian visa and residence permits into one single visa provision as the approval mechanism for foreign visitors to enter and stay in Indonesia’s territory. This study shows this integration scenario supports the proponent factors such as the current policies, systems, and practicality and simplification, and the public demand for improved public service delivery. Future work also should discuss the post-pandemic visa policy in Indonesia and the integration of other agencies’ application systems from the perspective of e-government.